Anesthesia-related mortality in pediatric patients: a systematic review - Leopoldo Palheta Gonzalez (Clinics, 2012)
This systematic review of the Brazilian and worldwide literature aimed to evaluate the incidence and causes of perioperative and anesthesia-related mortality in pediatric patients. Studies were identified by searching EMBASE (1951-2011), PubMed (1966-2011), LILACS (1986-2011), and SciElo (1995-2011). Each paper was revised to identify the author(s), the data source, the time period, the number of patients, the time of death, and the perioperative and anesthesia-related mortality rates. Twenty trials were assessed. Studies from Brazil and developed countries worldwide documented similar total anesthesia-related mortality rates (<1 death per 10,000 anesthetics) and declines in anesthesia-related mortality rates in the past decade. Higher anesthesia-related mortality rates (2.4-3.3 per 10,000 anesthetics) were found in studies from developing countries over the same time period. Interestingly, pediatric perioperative mortality rates have increased over the past decade, and the rates are higher in Brazil (9.8 per 10,000 anesthetics) and other developing countries (10.7-15.9 per 10,000 anesthetics) compared with developed countries (0.41-6.8 per 10,000 anesthetics), with the exception of Australia (13.4 per 10,000 anesthetics). The major risk factors are being newborn or less than 1 year old, ASA III or worse physical status, and undergoing emergency surgery, general anesthesia, or cardiac surgery. The main causes of mortality were problems with airway management and cardiocirculatory events. Our systematic review of the literature shows that the pediatric anesthesia-related mortality rates in Brazil and in developed countries are similar, whereas the pediatric perioperative mortality rates are higher in Brazil compared with developed countries. Most cases of anesthesiarelated mortality are associated with airway and cardiocirculatory events. The data regarding anesthesia-related and perioperative mortality rates may be useful in developing prevention strategies.